The Effectiveness of Audiovisual Media in Laboratory Learning on Improving Student Learning Outcomes during the Covid-19 Pandemic - Heryningsih, Wiwin Priyantari; Kuswanti, Ina; lubis, Dina putri utami (Trigin Institute, 2024)
Background: The COVID-19 pandemic has spread since the end of 2019 until now throughout the world. Educational institutions inevitably innovate face-to-face conventional learning into online distance learning. Online learning on cognitive achievement can be done, but a solution is needed for learning clinical skills both in the laboratory and in practice. This study aims to determine